On Jewish Folklore - Patai, Raphael (Wayne State University Press, 1983)
On Jewish Folklore spans a half-century of scholarly inquiry by the noted anthropologist and biblical scholar Raphael Patai. He essays collected in this volume, some of which are presented for the first time in English translation, provide a rich harvest of Jewish customs and traditional beliefs, gathered from all over the world and from ancient to modern times. Among the subjects Dr. Patai investigated and recorded are the history and oral traditions of the now-vanished Marrano community of Meshhed, Iran; cultural change among the so-called Jewish Indians of Mexico; beliefs and customs in connection with birth, the rainbow, and the color blue; Jewish variants of the widespread custom of earth-eating; and the remarkable parallels between the rituals connected with enthroning a new king as described in the Bible and as practiced among certain African tribes.